Fibrolytic enzyme production of Myceliophthora thermophila M.7.7. using inexpensive carbon sources and mineral nutrients - Moretti, Marcia Maria De Souza [UNESP]; Bonfa, Emily Colferai [UNESP]; Chierotti, Maria Cecilia Maia [UNESP]; Movio, Ariane Priscila [UNESP]; Silva, Roberto da [UNESP]; Gomes, Eleni [UNESP] (My University, 2014)
This study investigated the effect of inexpensive carbon and nitrogen sources on enzyme production by Myceliophthora thermophila M.7.7 in solid-state fermentation. Three kinds of lignocellulosic waste (corn straw, sugarcane bagasse and sugarcane straw) and six nitrogen sources (urea, calcium nitrate, analytical ammonium sulphate, yeast extract, agricultural fertilizer NPK 20-05-20 and fertilizing grade ammonium sulphate) were tested. Some physical-chermical parameters of the fermentation, such as temperature, initial pH and moisture content of the substrate on enzyme production, were evoluated. The maximum activities of xylanase (446.9 U/ml) endoglucanase (94.7 U/ml) and beta-glucosidase (2.8 U/ml) were observed in a mixture of corn straw and wheat bran (1:1 w/w) as the carbon source using fertilizer grade ammonium sulphate as the nitrogen source. This production occurred for an incubation period of 96 h, at 40°C, with initial moisture content of 70% and pH 5.0. These results have significant interest since they could be used for the future production of enzymes in a low-cost industrial process.
Keywords: Myceliophthora thermophila; solid-state fermentation; xylanase; endoglucanase; beta-glucosidase